Toward a Genealogy of Social Epistemology: Conceptual Origins and Re-invention of the Research Field - Sidorova, Stefaniia (Sententiae, 2025)
This article presents a historical-philosophical study of the formation of social epistemology as a distinct field. The author identifies two stages in its development: the initial conceptualization in 1950s library science (the project of Margaret Egan and Jesse Shera) and its reinvention in 1980s Anglophone philosophical discourse (the analytical project of Alvin Goldman, the critical project of Steve Fuller, and the collective project of Margaret Gilbert). Particular attention is given to the methodology of historico-philosophical analysis within social epistemology, and a novel anthropo-epistemological approach is proposed for constructing a chimerical genealogy. The author argues that social epistemology is not a homogeneous discipline but rather a spectrum of research projects. This study outlines the initial stage of social epistemology’s institutionalization and lays the groundwork for a critical historiography of the field.